Cation solvation in the solid state - temperature-dependent crystal structures in some metal perchlorates solvated by dimethylsulfoxide - Chan, E.; Cox, B.; Harrowfield, J.; Ogden, Mark; Skelton, B.; White, A. (Elsevier, 2004)
Problems arising from the extensive disorder characteristic of the crystalline lattice of dmso solvates of metal perchlorates at room temperature can in many cases be ameliorated or removed at "low" temperature. Present studies of several M(ClO4)n . 6dmso (n=2,3) species and Dy(ClO4)3 . 8dmso have allowed detailed definition of several homoleptic dmso-solvated metal cations, all of which contain dmso as an O-bound unidentate ligand and which appear to closely confirm the forms of solvated cations deduced from independent solution studies.